The U.S. Supreme Court : a very short introduction - Greenhouse, Linda (New York, NY : Oxford University Press, 2020)
For 30 years, Linda Greenhouse, the Pulitzer Prize-winning author, chronicled the activities of the justices as the Supreme Court correspondent for the New York Times. In this concise volume, she draws on her deep knowledge of the court's history as well as of its written and unwritten rules to show the reader how the Supreme Court really works.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 2, 2020).
Keywords: United States. -- Supreme Court; United States. -- Supreme Court -- History; Advice and Rights; Laws of specific jurisdictions & specific areas of law